Peran Kegiatan Praktik Berbasis Eksperimen Demonstrasi dalam Proses Pembelajaran di Sekolah Dasar - Muhamad Fajri; Junaidin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Practical activities are an effective learning approach to supporting the development of knowledge, skills, and attitudes in elementary school students. This article aims to examine the role of practical activities in the form of experiments and demonstrations in the learning process in elementary schools through a literature review. Data were obtained from various sources, including books, scientific journals, research articles, and educational documents relevant to the research topic. The results of the study indicate that experimental and demonstration activities play a significant role in improving students' conceptual understanding, science process skills, critical thinking skills, learning motivation, and scientific attitudes. Experimental activities provide opportunities for students to discover concepts through direct experience, while demonstrations help students understand processes or concepts that are difficult to observe independently. Furthermore, both methods can create more active, engaging, and meaningful learning, in accordance with the developmental characteristics of elementary school students who are still at the concrete operational stage. Therefore, the implementation of practical activities in learning needs to be continuously developed as part of a student-centered learning strategy.